Exploring college students' workload of critical thinking learning in online english reading courses - Huang, Qiuyang; Muhamad, Mohd Mokhtar; Che Nawi, Nur Raihan (Human Resources Management Academic Research Society (HRMARS), 2024)
This qualitative study explores how students who are taking online English reading classes deal with workload issues as they build their critical thinking skills. The study attempts to clarify the intricacies and significance of workload in the context of critical thinking learning through in-depth interviews, theme analysis, and the presenting of coded important results with quotes from participants.The study is essential to improving our comprehension of the complex interactions that exist between workload and critical thinking in online learning. Its importance stems from the fact that it not only addresses current issues regarding online English reading courses but also adds to the larger conversation about good teaching practices, student welfare, and the evolution of education in the digital age. The results could guide strategies that improve the effectiveness and quality of online learning, which would ultimately help students, teachers, and educational policymakers.